Hydatid cyst of common bile duct mimicking type 1 choledochal cyst - De Utpal; Basu Mina (Wolters Kluwer Medknow Publications, 2007)
A 11 year-old girl presented with pain in the abdomen, an abdominal mass and jaundice. Clinical examination and investigations suggested a diagnosis of a type 1 choledochal cyst. Upon operation, a solitary, unruptured hydatid cyst was found obstructing the common bile duct. Intrinsic obstruction of the extrahepatic bile duct by a solitary hyatic cyst without any hepatic involvement as seen in this unique case, has not been reported until now.